Haemopoietic cell growth factor mediates cell survival via its action on glucose transport. - Whetton, A D (1984)
A number of haematopoietic precursor cell lines have been established which exhibit an absolute dependence on haematopoietic cell growth factor (HCGF) which is secreted by WEHI-3 myelomonocytic leukaemia cells. In the presence of HCGF, ATP levels are maintained in these factor-dependent cells (FDC-P cells); in the absence of HCGF, intracellular ATP levels undergo a steady depletion. The cell death that follows this ATP depletion can be prevented by supplying exogenous ATP suggesting that HCGF maintains these cells via its effects on energy metabolism. We have investigated the effect of HCGF on FDC-P cells further and found that: (i) HCGF markedly and rapidly increases lactate production; (ii) high extracellular glucose or glycolytic intermediate concentrations can maintain FDC-P cell viability to some extent whilst stimulating lactate production; (iii) the uptake of 2-deoxyglucose by FDC-P2 cells is stimulated by HCGF in a dose-dependent fashion. This uptake is inhibited by cytochalasin B; (iv) HCGF does not stimulate L-glucose uptake by FDC-P cells. These results suggest that HCGF acts to maintain FDC-P cells via its action on glucose transport. The significance of these results to haemopoiesis and leukaemogenesis is discussed.